2011
DOI: 10.1371/journal.pgen.1002233
|View full text |Cite
|
Sign up to set email alerts
|

Ku Must Load Directly onto the Chromosome End in Order to Mediate Its Telomeric Functions

Abstract: The Ku heterodimer associates with the Saccharomyces cerevisiae telomere, where it impacts several aspects of telomere structure and function. Although Ku avidly binds DNA ends via a preformed channel, its ability to associate with telomeres via this mechanism could be challenged by factors known to bind directly to the chromosome terminus. This has led to uncertainty as to whether Ku itself binds directly to telomeric ends and whether end association is crucial for Ku's telomeric functions. To address these q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(76 citation statements)
references
References 59 publications
5
70
1
Order By: Relevance
“…1A) (41). Consistent with published results, Ku-RE was found to be partially defective in binding blunt dsDNA ends when analyzed by an EMSA (Fig.…”
Section: Requirement For the Dna End-binding Activity Of Ku In Exo1supporting
confidence: 91%
“…1A) (41). Consistent with published results, Ku-RE was found to be partially defective in binding blunt dsDNA ends when analyzed by an EMSA (Fig.…”
Section: Requirement For the Dna End-binding Activity Of Ku In Exo1supporting
confidence: 91%
“…Resection is almost completely inhibited in angiosperm plants, resulting in telomeres with no or only a few-nucleotide long G-overhangs. Studies in budding yeast demonstrated that Ku physically associates with and protects chromosome termini in nondividing cells (Bonetti et al 2010;Vodenicharov et al 2010) and that telomeric function requires direct loading of Ku onto DNA through a circular channel in its structure (Lopez et al 2011;Pfingsten et al 2012). Blunt-ended telomeres generated by the leading strand replication are perfect substrates for Ku loading, which may be occluded after resection by proteins that bind to ssDNA (Faure et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…At least three different complexes contribute to the capping function and prevent telomeres from being recognized as DSBs: Rap1-Rif1-Rif2 bound to double-stranded telomeric repeats 7,8 , the CST (Cdc13, Stn1, Ten1) complex that covers the G-tail [9][10][11] and the Ku heterodimer that directly binds to the terminal telomeric DNA 12,13 . One role of these complexes is to control the action of the nucleases/helicases involved in DSB resection 14 .…”
mentioning
confidence: 99%